2018
DOI: 10.1155/2018/5492527
|View full text |Cite
|
Sign up to set email alerts
|

Erector Spinae Plane Block for Elective Laparoscopic Cholecystectomy in the Ambulatory Surgical Setting

Abstract: Postoperative pain after laparoscopic cholecystectomy can be severe. Despite multimodal analgesia regimes, administration of high doses of opioids is often necessary. This can further lead to several adverse effects such as drowsiness and respiratory impairment as well as postoperative nausea and vomiting. This will hinder early mobilization and discharge of the patient from the day surgery setting and is suboptimal in an Early Recovery after Surgery setting. The ultrasound-guided Erector Spinae Plane (ESP) bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 25 publications
1
31
0
4
Order By: Relevance
“…It blocks the thoracolumbar nerves T10 to L1 and provides adequate somatic analgesia with little or no visceral blockade. [ 3 ] Another technique is ESP block, which blocks the ventral as well as dorsal branches of the spinal nerves[ 10 11 ] along with the communicating branches that augment the sympathetic chain catering sympathetic block and to visceral analgesia. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…It blocks the thoracolumbar nerves T10 to L1 and provides adequate somatic analgesia with little or no visceral blockade. [ 3 ] Another technique is ESP block, which blocks the ventral as well as dorsal branches of the spinal nerves[ 10 11 ] along with the communicating branches that augment the sympathetic chain catering sympathetic block and to visceral analgesia. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral ESPB has also been reported to be used in many upper and lower abdominal laparoscopic procedures, including laparoscopic sleeve gastrectomy, samesession laparoscopic cholecystectomy and inguinal hernia plus endoscopic retrograde cholangiopancreatography, laparoscopic varicocelectomy, laparoscopic hepatic cyst, laparoscopic nephrectomy, laparoscopic hysterectomy, laparoscopic Nissen fundoplication, laparoscopic hysterectomy, laparoscopic ovarian cystectomy, and laparoscopic hemicolectomy. 7,19,22,28,[63][64][65][66][67] However, in some cases bilateral ESPB has been reported to result in block failure or lack of efficiency. 28…”
Section: Open Abdominal Surgeriesmentioning
confidence: 99%
“…Studies have shown that the spread of LA in the paravertebral space in the cephalic and caudal direction can lead to analgesia from C7-T2 to L2-3 [4]. For that reason the block was successfully used in acute pain management in pneumothorax surgery (ESP block at T6 level) [26], applied in video-assisted thoracoscopic surgery (VATS) [27], minimally invasive mitral valve surgery via thoracotomy incisions (ESP block at the level of the T7 transverse process) [8], postoperative analgesia after caesarean section (at T9 level) [28], postoperative analgesia in retropubic radical prostatectomy (over the 12th thoracic vertebrae) [29], different laparoscopics abdominal surgeries [19], laparoscopic cholecystectomy in the ambulatory setting [30] and bariatric surgery [17], as examples.…”
Section: Thoracic and Abdominal Chronic And Acute Pain Managementmentioning
confidence: 99%